ASSOCIATION BETWEEN RS731236 POLYMORPHISM OF THE VITAMIN D RECEPTOR (VDR) GENE AND THE DEVELOPMENT OF PROLIFERATIVE BENIGN DYSPLASIA OF THE MAMMARY GLAND IN WOMEN FROM THE SUMY REGION, UKRAINE - Harbuzova, Viktoriia; Kyrychenko, Mykola; Lukavenko, Ivan; Obukhova, Olha (Eastern Ukrainian Medical Journal, 2024)
Introduction. Benign proliferative breast dysplasia (BPBD) is a common women’s health issue, the frequency of which can reach up to 95% among women of reproductive age. BPBD can be complicated by the development of breast cancer (BC), the risk of which with atypical proliferation can increase by 4.24 times. One of the modern directions of BPBD diagnostics is the search for genetic markers of the disease. The promising direction is represented by polymorphic variants of the vitamin D receptor (VDR) gene – a nuclear receptor that regulates the expression of genes involved in the processes of cell differentiation and proliferation and apoptosis and plays an important role in the pathogenesis of precancerous and tumor diseases. To date, more than 25 thousand VDR gene polymorphisms have been studied, some of which, in particular rs731236, are associated with the development of benign and malignant tumor diseases. Objective. The aim of the study was to study the distribution of rs731236 polymorphic variants of the VDR gene in patients with BPBD from the Sumy region of Ukraine. Materials and Methods. The study used venous blood from 326 women living in the Sumy region of Ukraine (221 patients with BPBD and 105 people without this pathology). Genotyping of patients and control group subjects for the rs731236 polymorphism of the VDR gene was performed using polymerase chain reaction followed by restriction fragment length polymorphism (PCR-RFLP). Statistical analysis of the results was performed using SPSS software (version 25.0). Results. The distribution of genotypes according to the rs731236 polymorphism of the VDR gene in the group of patients with BPBD was as follows: T/T – 71 (31.2%), T/t – 113 (51.1%), t/t – 37 (16.8%); in the control group, these were 44 (41.9%), 52 (49.5%), and 9 (8.6%), respectively. Statistically significant differences in allele frequencies for the comparison groups were found (P = 0.028; χ2 =4.801): the frequency of the minor allele in the main group equaled 42.3%, and in the control group – 33.3%. The logistic regression method showed that recessive t/t homozygotes had a higher risk of developing BPBD compared to dominant T/T homozygotes according to the additive model (P = 0.025). The association remained statistically significant after adjusting for age and BMI (P = 0.031). Conclusions. In the Sumy region of Ukraine, the minor t‑allele for the rs731236 polymorphism of the VDR gene was significantly more common in women with BPBD than in women without BPBD (P = 0.028), and the t/t genotype was a risk factor for the development of BPBD: recessive homozygotes (t/t) had a higher risk of developing BPBD compared to dominant homozygotes T/T (P = 0.025). Patients under 40 years of age with the t/t genotype had a higher risk of developing BPBD compared to women with the T/T genotype (P = 0.025). Individuals with normal BMI and the minor allele t in their genotype had a higher risk of developing BPBD (P = 0.042 for dominant, P = 0.028 for recessive, P = 0.007 for additive inheritance models).